Patient Barriers and Facilitators to Ambulatory and Home Blood Pressure Monitoring: A Qualitative Study. (18th May 2018) - Carter, Eileen J; Moise, Nathalie; Alcántara, Carmela; Sullivan, Alexandra M; Kronish, Ian M
Abstract: BACKGROUND: Guidelines recommend that patients with newly elevated office blood pressure undergo ambulatory blood pressure monitoring (ABPM) or home blood pressure monitoring (HBPM) to rule-out white coat hypertension before being diagnosed with hypertension. We explored patients' perspectives of the barriers and facilitators to undergoing ABPM or HBPM. METHODS: Focus groups were conducted with twenty English- and Spanish-speaking individuals from underserved communities in New York City. Two researchers analyzed transcripts using a conventional content analysis to identify barriers and facilitators to participation in ABPM and HBPM. RESULTS: Participants described favorable attitudes toward testing including readily understanding white coat hypertension, agreeing with the rationale for out-of-office testing, and believing that testing would benefit patients. Regarding ABPM, participants expressed concerns over the representativeness of the day the test was performed and the intrusiveness of the frequent readings. Regarding HBPM, participants expressed concerns over the validity of the monitoring method and the reliability of home blood pressure devices. For both tests, participants noted that out-of-pocket costs may deter patient participation and felt that patients would require detailed information about the test itself before deciding to participate. Participants overwhelmingly believed that out-of-office testing benefits outweighed testing barriers, were confident that they could successfully complete either testing if recommended by their provider, and described the rationale for their testing preference. CONCLUSIONS: Participants identified dominant barriers and facilitators to ABPM and HBPM testing, articulated testing preferences, and believed that they could successfully complete out-of-office testing if recommended by their provider.